Sustainability life of lobster (sp. Locusta) in the coral reef NRF Sancang Area - Sugandi Dede (E3S Web of Conferences)
Lobsters are shallow water organisms and are often caught by fishermen traditionally. The aim of the research is to analyze natural lobster catching, the sustainability of lobsters (sp.locusta) and baby lobsters (sp.infantem locustam) and forms of coral reef conservation in the NRF Sancang area. The method used is descriptive with qualitative interviews. Mapping of the NRF of Sancang coral reef area by analyzing Landsat 8 images in 2023, ground checks and interviews. Tracing is done at night using boats, nets and petromak or LED lights with the aim that the lobsters (sp.locusta) will get closer to the center of the light. Lobster (sp.locusta) has a high selling value, so it attracts fishermen to catch both baby lobsters (sp.infantem locustam) and their mothers. Adult lobsters are sold for consumption, while baby lobsters (sp.infantem locustam) are sold outside the region and even abroad to be kept, which threatens the sustainability of lobsters (sp.locusta) in the HCA Sancang coral reef area. Because of this, conservation is needed by implementing strict regulations.